An in-vitro assessment of the retrievability of fractured dental implant abutment screws - Moorthy, Advan (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2021)
Background: Fractured abutment screws have the potential to preclude restoration of osseointegrated dental implants and as a result, a wide range of products and techniques aimed at retrieving fractured screw fragments were reported. Establishing a standard treatment protocol for retrieving fractured abutment screw fragments is difficult and few experimental in-vitro trials have been published. Currently, there is no consensus regarding the efficacy and risk assessment of the reported techniques and clinical incidents of abutment screw fracture are usually managed tentatively. Aims: The aims of this in-vitro study were: (1) To compare the efficacy of a commercially available universal screw retrieval kit with a homemade screw retrieval kit in retrieving fractured abutment screw fragments from dental implants. (2) To assess the effect of dental implant system type, operator experience, screw fracture morphology, screw fracture torque and location of the implant on the ability to retrieve fractured abutment screw fragments from dental implants. Materials and methods: A total of 64 implants had fractured abutment screws placed. Retrieval of the fractured abutments screw fragments took place in a designated dental chair unit where a phantom head containing the specimen was attached. A successful attempt to retrieve a fractured screw fragment was defined as the complete removal of the screw fragment within 15 mins with no damage to the internal threads of the implant. The following data were recorded for each experimental specimen: operator experience level (inexperienced or experienced), dental implant system (Straumann ® or Nobel Biocare ®), implant position (maxillary anterior, maxillary posterior, mandibular anterior or mandibular posterior sextant), fracture morphology type of the fractured screw fragment (type 1, 2, 3 or 4), type of retrieval kit used (commercially available screw retrieval kit or homemade retrieval kit), torque at which the screw fractured (Ncm), retrieval outcome (screw fragment retrieved: yes/no), time taken to retrieve the screw fragment (secs), presence of damage to implant threads (yes/no). Retrieval outcome and the time taken were analysed by means of descriptive statistics, Fisher s exact tests, a binary logistic regression, Mann-Whitney U tests, Kruskal-Wallis association tests and a Spearman's rank-order correlation test where appropriate. The level of significance was set at 5% (p < 0.05). Results: The retrieval success rate overall was 89.1%. No significant differences were found in retrieval outcome in relation to the different categorical variables tested. The mean time required to successfully retrieve the fractured abutment screw fragments was 3 mins 12 secs (SD: 3 mins 13 secs). No significant differences were found in retrieval times in relation to the retrieval kit used, the operator s experience or the implant s position. Retrieval times for the screw fragments from the Nobel Biocare ® implant system was longer than for the Straumann® implant system (U = 615.500, p = 0.001) but were clinically insignificant. Similarly, the retrieval time for fractured screw fragments with a type 1 fracture morphology was longer than those with a type 2 fracture morphology (p = 0.002) but were clinically insignificant. A weak positive correlation between the torque value at which the abutment screws fractured and the retrieval time was found (rs = 0.300, p = 0.023). Conclusion: The results indicated that fractured abutment screw fragments may be removed safely and in a reasonably short period of clinical time. The combination of standard dental instruments and modified standard dental instruments found in the homemade screw retrieval kit used in the study were as effective in the retrieval of fractured abutment screw fragments as the commercially available universal abutment screw retrieval kit. Operators that are inexperienced in retrieving fractured abutment screw fragments from dental implants may overcome this clinical complication as easily as experienced operators.
APPROVED